Adventures of Portuguese 'ancient music' in Oxford, London and Paris: Duarte Lobo's 'Liber missarum' and musical antiquarianism, 1650-1850 - Rees, O (Oxford University Press, 2005)
Works from the Liber missarum (Antwerp, 1621) of the Portuguese composer Duarte Lobo (c.1565-1646) became established in the repertory of 'ancient music' cultivated in eighteenth-century England. In particular, the motet Audivi vocem de caelo enjoyed considerable and long-lasting popularity, indicated by numerous manuscript copies, published editions, and records of performances. Such familiarity with Lobo's works probably stemmed from a copy of the Liber missarum presented to the Bodleian Library in 1659, and later consulted by William Walond senior and Henry Needler. Perhaps thanks to Needler, Lobo's music entered the repertory of the Academy of Ancient Music. Other manuscript copies of Lobo's works are by John Immyns, founder of the Madrigal Society; Audivi vocem featured in the Society's repertory well into the nineteenth century. In 1827 Vincent Novello published an edition of Audivi vocem, and further editions appeared in Paris and England during the 1840s. Aspects of how the piece was performed can be established from manuscript annotations.